DEVELOPMENT AND VALIDATION OF RP-UPLC AND DERIVATIVE SPECTROPHOTOMETRIC METHODS FOR QUANTITATIVE DETERMINATION OF ASCORBIC ACID AND N-ACETYLCYSTEINE IN EFFERVESCENT TABLETS: Pharmaceutical Science-Analytical Chemistry - KUCUK TUNCA, AYSEL; MERVE OZARAZ (International Journal of Life Science and Pharma Research, 2019)
In this study, reverse phase-ultra performance liquid chromatographic (RP-UPLC) and first derivative spectrophotometric methods were developed and validated for the simultaneous determination of ascorbic acid (AA) and n-acetylcysteine (NAC) quantities in effervescent tablets. Liquid chromatography tests were carried out isocratically with the UPLC BEH C18 column. Analyzes were completed in a short time (approximately 6 minutes) with the developed method. UV detector at 220 nm (detection wavelength) was used and the mobile phase was composed of acetonitrile and phosphate buffer (1:99, v/v, pH 2.5). Linearity ranges in methods were 3-60 µg mL-1 for AA and 6-84 µg mL-1 for NAC. Retention times were 1.59 and 4.61 min for AA and NAC, respectively. First derivative spectrophotometry was employed as a second analytical method and AA and NAC derivative spectra were recorded at 285 nm and 222.5 nm respectively. High recovery values were obtained for AA and NAC. The methods developed were validated for the parameters of linearity, accuracy, precision, specificity, sensitivity, the limit of quantitation, the limit of detection and recovery as defined in the ICH analytical method validation guidelines. Then, the methods were successfully applied to routine analysis for the determination of AA and NAC in commercial effervescent tablets without any interference by the excipients. These methods are also advantageous in that they do not require a pre-separation process for analysis. Furthermore, a large number of samples could be analyzed quickly with this method due to the short chromatographic analysis time. Finally, the results were evaluated statistically and the methods were compared with each other.